Biomechanical analysis to improve the grab starting performance for the freestyle 50-meter women swimmers - Mohamed Tawfik Mohamed, R. (World Journal of Sport Sciences, 2010)
The purpose of this study was to improve the starting time (grab start) of the freestyle 50-meter women swimmers and to reach predictive mathematical equations representing a scientific basis to improve the starting time. 3 women swimmers from the Port Said University team, selected by the deliberate way, as each swimmer performed three 50-meter swimming trials from above the starting block before performing the specific trainings to improve the performance of the Grab Starting. The results suggested that to obtain a faster start, swimmers should (a) perform the grab start quickly and strongly to help finishing the race distance in less time due to the optimum use of the strong resistance of the starting block in giving the body the maximum speed and efficiency to attain the maximum push power forward, (b) perform the specific exercise for the muscles of legs as it is principally responsible for the positive motor result for the swimmers during start, (c) improving the grab start as it is possible to decrease the race time by 0.10 seconds, (d) keeping the body of the swimmer closer to a straight line as much as possible in order to lessen the fractures that hindrance the smooth movement to achieve the highest possible benefit that helps the swimmer to achieve the farthest distance from the starting block and (e) the swimmer should enter the water with a slope, which gives a bigger chance in the slipping into the water, hence achieving the best distance inside the water and achieving the best time.